Climate-Smart Villages: Key Concepts. A primer for CCAFS partners in Southeast Asia - Gonsalves, Julian Francis; Sebastian, Leocadio S.; Joven, B.P.; Amutan C; Lucerna A (International Institute of Rural Reconstruction, 2015)
Understanding the impacts of climate change on agriculture, associated landscapes and natural resources in general is crucial if local development efforts are to be tailored towards addressing the impacts of climate change. Simplification of scientific concepts can help local planners at different level to introduce and then mainstream strategies that have factored in the impacts from climate change